Recurrent stroke in symptomatic carotid stenosis awaiting revascularization: A pooled analysis. (9th February 2016) - Johansson, Elias; Cuadrado-Godia, Elisa; Hayden, Derek; Bjellerup, Jakob; Ois, Angel; Roquer, Jaume; Wester, Per; Kelly, Peter J.
Abstract : Objective: We aimed to quantify the risk and predictors of ipsilateral ischemic stroke in patients with symptomatic carotid stenosis awaiting revascularization (carotid endarterectomy [CEA] or carotid artery stenting) by pooling individual patient data from recent prospective studies with high rates of treatment with modern stroke prevention medications. Methods: Data were included from 2 prospective hospital-based registries (Umeå, Barcelona) and one prospective population-based study (Dublin). Patients with symptomatic 50%–99% carotid stenosis eligible for carotid revascularization were included and followed for early recurrent ipsilateral stroke or retinal artery occlusion (RAO). Results: Of 607 patients with symptomatic 50%–99% carotid stenosis, 377 met prespecified inclusion criteria. Ipsilateral recurrent ischemic stroke/RAO risk pre-revascularization was 2.7% (1 day), 5.3% (3 days), 11.5% (14 days), and 18.8% (90 days). On bivariate analysis, presentation with a cerebral vs ocular event was associated with higher recurrent stroke risk (log-rank p = 0.04). On multivariable Cox regression, recurrence was associated with older age (adjusted hazard ratio [HR] per 10-year increase 1.5, p = 0.02) with a strong trend for association with cerebral (stroke/TIA) vs ocular symptoms (adjusted HR 2.7, p = 0.06), but not degree of stenosis, smoking, vascular risk factors, or medications. Conclusions: We found high risk of recurrent ipsilateral ischemic events within the 14-day time period currently recommended for CEA. Randomized trials are needed to determine the benefits and safety of urgent vs subacute carotid revascularization within 14 days after symptom onset.